Peramalan Permintaan Printing Menggunakan Metode Double Exponential Smoothing dan Pengujian Hasil Menggunakan Grafik Tracking Signal pada PT. XYZ - Sindy Anggraeni; Jauhari Arifin (Peneliti.net, 2022)
PT. XYZ is a company engaged in make-to-order-based printing services. In MTO-based companies, forecasting can be used to prevent unfulfilled consumer demand and inventory. The purpose of this study is to obtain the best forecasting results using the double exponential smoothing method based on the smallest MSE value and verify the forecasting results using the tracking signal method. Based on the results of the analysis and discussion, it is found that the double exponential smoothing method with parameter value =0.2 was chosen because it has the smallest MSE value of 5712904.8. forecasting results for the next 3 months, namely January to March 2022, have increased successively by 5491, 5724, 5956. Forecasting using double exponential smoothing with parameter value =0.2 is still within the tracking signal control limit, namely (±4).